An Investigation of the Atmospheric Boundary Layer over the Arctic Ocean Using SODAR (Sound Detection and Ranging). - Rouge,Etienne de (1985)
An attempt to describe the atmospheric boundary layer during the (Marginal Ice Zone Experiment) MIZEX 84 from 11 July to 17 July was made using a sodar system. The computation of the temperature structure parameter CT2 in the surface layer using in situ measurements allowed the calibration of the system. A program was developed to obtain the inversion layer height Zi, where the signal reaches a maximum. The thickness of the inversion layer was also computed and was used with the calibration law to compute CT(2) at the inversion layer. Refractive trapping conditions were evident on 15 July although the generally small value of the heat flux did not indicate a strongly unstable boundary layer. Comparison with two radiosonde profiles shows good agreement in one case. It is the purpose of this thesis to calibrate the sodar system deployed by the research vessel POLAR QUEEN during MIZEX 84 to obtain the refractive-index structure parameter. The tme-height structure of the boundary layer will also be investigated. Efforts will also be made to compute the height of the inversion layer and to estimate its thickness, the jump of potential temperature, and the refractive-index gradient. Abstract in French.